Temperature-resistance sensor arrays for combinatorial study of phase transitions in shape memory alloys and metallic glasses. (15th July 2019) - Zheng, Juanjuan; Zhang, Haitao; Miao, Yucong; Chen, Shi; Vlassak, Joost J.
Abstract: We have developed sensor arrays using a simple and inexpensive fabrication process to measure the electrical resistance of thin-film materials as a function of temperature and composition. The sensors are capable of characterizing materials from liquid‑nitrogen temperature to approximately 900 K and are not limited by low sample conductivity. We demonstrate the sensitivity and accuracy of the technique by analyzing the phase evolution in Ti-Ni-Cu shape memory alloys and PdSi-based metallic glasses. For the latter, we find that the change in resistance on crystallization correlates with glass-forming ability. This observation may be useful in identifying good glass formers using high-throughput techniques. Graphical abstract: Unlabelled Image